Torsion of the gallbladder in a child - Gürses, Naci; Büyükpamukçu, Nebil; Hiçsönmez, Akgün (The Turkish Journal of Pediatrics, 1979)
Torsion of the gallbladder was reported in a 7 year old boy, with a brief review of the literature.